Great trails of the West - Dunlop, Richard (Abingdon Press Nashville, 1971)
Modern day historical tour along 15 trails of the western frontier.
The West -- Santa Fe trail: Journey to Sundown -- Santa Fe Trail: Mountain Branch -- Santa Fe Trail: Cimarron cutoff -- El Camino Real: the old San Antonio Road -- Royal road to the California Missions -- Oregon trail: Across the plains -- Oregon trail: The North platte -- Oregon trail: South pass and Beyond -- Barlow Road -- Hasings cutoff -- California Trail -- Mormon Trail -- the Applegate Road -- Lassen Trail: Norhern Route to the Goldfields -- Nobles Road to Old Shasta -- Butterfield Trail: Nothing must stop the mail -- Butterfield Trail: A wolf could not make his living -- Pony Express trail -- Mullan Road to the gold camps -- Chisholm Trail -- Chilkoot Trail -- Bibliography -- Index
Includes Index
Keywords: Trails -- West (U.S.); West (U.S.) -- Description and travel; Overland journeys to the Pacific